The transition from work to retirement - Werner Eichhorst (Institute for the Study of Labor (IZA), 2011)
The European Employment Strategy has set the goal of raising the retirement age of workers in the EU through a strategy of active ageing. Yet despite some progress over the last decade, empirical data show persistent diversity across EU member states. Institutional arrangements of social and labor market policies can be seen as the core factors behind cross-national diversity. Hence, institutional change is crucial to explain structural changes. The paper tries to assess the role of supranational policy initiatives and national politico-economic factors in shaping the transition from work to retirement in EU member states which is still governed by the national political economy. Taking the German case as an example in point, the paper shows the dynamic interaction between policy changes, in particular in benefit systems and activation, and changes in the approach of firms and workers to early retirement. Policy changes influence actors' behavior in the medium run and open up opportunities for subsequent reforms.
urn:nbn:de:101:1-201104113633
Keywords: J14; J26; 330; early retirement; older workers; Germany; European Employment Strategy; Flexible Altersgrenze; Ältere Arbeitskräfte; Beschäftigungspolitik; EU-Politik; Nationalstaat; Vergleich; EU-Staaten; Deutschland